2008
DOI: 10.1111/j.1365-2966.2008.13781.x
|View full text |Cite
|
Sign up to set email alerts
|

VW LMi: tightest quadruple system known. Light-time effect and possible secular changes of orbits

Abstract: Tightest known quadruple system VW LMi consists of contact eclipsing binary with P12= 0.477 551 d and detached binary with P34= 7.930 63 d revolving in rather tight, 355.0‐d orbit. This paper presents new photometric and spectroscopic observations yielding 69 times of minima and 36 disentangled radial velocities for the component stars. All available radial velocities and minima times are combined to better characterize the orbits and to derive absolute parameters of components. The total mass of the quadruple… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 24 publications
3
27
0
Order By: Relevance
“…We reproduced the stellar and orbital parameters derived by Casey et al (1998) based on the 2009 VYSOS6 data (Fig. 1) using the methods of Pribulla et al (2008). It can be noticed that the secondary minimum at a phase of ≈ 0.5 already becomes more pronounced in the R and I bands, compared to the B and V bands.…”
Section: Overviewmentioning
confidence: 82%
“…We reproduced the stellar and orbital parameters derived by Casey et al (1998) based on the 2009 VYSOS6 data (Fig. 1) using the methods of Pribulla et al (2008). It can be noticed that the secondary minimum at a phase of ≈ 0.5 already becomes more pronounced in the R and I bands, compared to the B and V bands.…”
Section: Overviewmentioning
confidence: 82%
“…On the other hand, the RV and timing-variability analysis of Pribulla et al (2008) showed that except the dynamically-induced apsidal motion in the DNEB, no perturbations could be detected in 10 years of observations. The analysis showed that the inclinations of the inner and outer orbits are similar.…”
Section: Perturbations Of Orbits In Multiple Systemsmentioning
confidence: 90%
“…The binaries revolve in a tight mutual outer orbit with P1234 = 355 days. Later, Pribulla et al (2008) determined the masses of all four components by simultaneous modelling of 4 radial-velocity (RV) curves and timing variability of the CEB caused by the light-time effect (LiTE) in the outer mu- Table 1. Overview of identifications and basic parameters of VW LMi.…”
Section: Introductionmentioning
confidence: 99%
“…During the DDO survey, we detected not only many triple systems: Some complex, close quadruple systems were observed as well. Among them, worth pointing out is the very interesting system of VW LMi with the outer orbit of 355 days [34,49].…”
Section: Triple Systemsmentioning
confidence: 99%